Investigating the mix of strategic choices and performance of transaction platforms: Evidence from the crowdfunding setting - Dushnitsky, Gary; Piva, Evila; Rossi‐Lamastra, Cristina (Strategic Management Journal, 2022)
Abstract Research Summary The platform literature offers keen insights on the pricing and non‐pricing strategies that transaction platforms undertake. We supplement this work by studying how platforms mix together their strategic choices and the association with platforms’ performance. To that end, we focus on crowdfunding platforms; a prominent setting of transaction platforms. We present an inductive large‐N study of the population of 788 crowdfunding platforms that operated in EU‐15 countries up to 2018. Our contribution is threefold: (a) identifying common mixes of strategic choices; (b) tracking deviations from these mixes; and (c) associating these with platforms’ survival and growth. We discuss our findings and how they advance knowledge at the intersection of the platform and strategic management literatures. Managerial Summary Notable transaction‐platforms such as eBay, LinkedIn, and Tencent have an aggregate market‐value in the hundreds of billions of dollars. We know that platforms’ success is driven by the strategic choices they undertake. Yet, we know less about how they mix together these choices and the association with platforms’ performance. Our study addresses this gap by focusing on a prominent setting: crowdfunding. Using data on the population of 788 crowdfunding platforms in EU‐15 countries, we show that these platforms cluster around three common mixes of strategic choices. Moreover, crowdfunding platforms do not strictly adhere to the strategy mix they are affiliated with. Interestingly, there is a positive association between the degree to which a platform's choices differentiate from its strategy mix and platform's subsequent performance.